Increasing HIV treatment access, uptake and use among men who have sex with men in urban Indonesia: evidence from a qualitative study in three cities. Issue 1 (18th October 2019) - Lazuardi, Elan; Newman, Christy E; Anintya, Irma; Rowe, Emily; Wirawan, Dewa N; Wisaksana, Rudi; Subronto, Yanri W; Kusmayanti, Nur Aini; Iskandar, Shelly; Kaldor, John; Bell, Stephen
Abstract: Men who have sex with men make up one of four key populations identified as critical to a successful HIV response in Indonesia. Despite international policies supporting HIV treatment in low- and middle-income countries, Indonesia is one of the few countries experiencing low coverage of HIV treatment and little decrease in HIV incidence. There is poor retention in care and low viral suppression rates among key populations such as men who have sex with men. The national government has committed to increasing treatment access and uptake for people with HIV but little is known about how these men themselves view, use and experience these medications. Drawing on qualitative data collected in 2015–16 from 24 HIV-positive men who have sex with men living in three Indonesian cities, we observed multiple intersecting social and contextual factors that can influence effective HIV treatment use. Although shared stories of strong side effects and fear of unwanted disclosure inhibited treatment uptake, social support from 'buddies' helped to navigate healthcare systems and sharing medication among peers enabled adherence. In order to improve treatment uptake and adherence among Indonesian men who have sex with men living with HIV, these divergent effects of the social meanings and practices associated with HIV treatments in Indonesia must be better acknowledged. A more comprehensive understanding of social and community practices within key populations can strengthen national efforts to improve treatment access and increase adherence. Ongoing decentralization of healthcare in Indonesia, and differentiated care models that enable initiation of treatment in community settings and involve non-medical, community-based organizations in the provision of treatment services have the potential to address the needs of individuals who fall into a key population category such as men who have sex with men.